2022
DOI: 10.3390/md20100621
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Starvation Enhances the Production of Saturated and Unsaturated Fatty Acids in Aurantiochytrium sp. PKU#SW8 by Regulating Key Biosynthetic Genes

Abstract: Nitrogen deprivation is known to improve lipid accumulation in microalgae and thraustochytrids. However, the patterns of fatty acid production and the molecular mechanisms underlying the accumulation of unsaturated and saturated fatty acids (SFAs) under nitrogen starvation remain largely unknown for thraustochytrids. In this study, batch culture experiments under nitrogen replete and nitrogen starvation conditions were performed, and the changes in the transcriptome of Aurantiochytrium sp. PKU#SW8 strain betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Filter paper and 1% CMC-Na were used as the substrates, respectively. The strains were first cultured in an M4 medium ( 92 ) at 28°C until the logarithmic growth phase to obtain seed cultures for quantification of cellulase activity. The seed culture (3 mL) was centrifuged at 4,000 rpm at 25°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Filter paper and 1% CMC-Na were used as the substrates, respectively. The strains were first cultured in an M4 medium ( 92 ) at 28°C until the logarithmic growth phase to obtain seed cultures for quantification of cellulase activity. The seed culture (3 mL) was centrifuged at 4,000 rpm at 25°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Early researchers improved intracellular lipid production by optimizing the fermentation conditions for thraustochytrids. They found that stress conditions such as low temperature (Ma et al, 2017), low or high dissolved oxygen (Sun et al, 2016;Heggeset et al, 2019) and nitrogen starvation (Chen et al, 2022) could stimulate the accumulation of intracellular lipids. Laboratory domestication and phased cultivation strategies (Wang et al, 2021a;Chen et al, 2022) have been developed.…”
Section: Ecological Insights: Unraveling the Compositional Complexity...mentioning
confidence: 99%
“…They found that stress conditions such as low temperature (Ma et al, 2017), low or high dissolved oxygen (Sun et al, 2016;Heggeset et al, 2019) and nitrogen starvation (Chen et al, 2022) could stimulate the accumulation of intracellular lipids. Laboratory domestication and phased cultivation strategies (Wang et al, 2021a;Chen et al, 2022) have been developed. Additionally, the inclusion of lipase inhibitors (Orlistat) (Ma et al, 2021), antioxidants (Zhang et al, 2020) and plant hormones (Yu et al, 2016) in the culture medium can influence PUFAs metabolism and promote lipid accumulation.…”
Section: Ecological Insights: Unraveling the Compositional Complexity...mentioning
confidence: 99%
“…Therefore, the use of these microorganisms has been widely proposed as a strategy to develop functional foods and feeding technology. Although many studies have shown that these protists are efficient in producing and accumulating PUFAs [ 16 , 17 , 18 , 19 ], the quantity produced is still not enough to cover the needs of the aquaculture industry [ 7 , 19 ]. Therefore, it is still necessary to optimize the production process in order to enrich the content of PUFAs in protists.…”
Section: Introductionmentioning
confidence: 99%